Addressing Corruption in All its Forms Through Sustainable Development Goals: A Bibliometric Analysis - Rassanjani, Saddam; Nofriadi, Nofriadi (Association of Certified Fraud Examiners Indonesia Chapter, 2025)
Corruption is a significant obstacle to sustainable development, weakening governance and public trust while deepening poverty and inequality. This paper examines global views on fighting corruption in all its forms through the lens of the Sustainable Development Goals (SDGs). Using bibliometric analysis in VOSviewer, the study reviews 112 scholarly articles across diverse disciplines to identify key trends, influential studies, and gaps in current research. The findings indicate an increasing academic interest in the relationship between corruption and sustainable development, with notable contributions from the UK, the US, and South Africa. The analysis underscores the crucial role of anti-corruption initiatives, particularly those aligned with SDG 16, in advancing the broader SDG agenda. By identifying emerging themes and overlooked areas, this study provides insights that can inform future research and strengthen cooperation among governments, civil society, and the private sector to promote transparency, accountability, and effective governance.